The usefulness of low radiation dose subtraction coronary computed tomography angiography for patients with calcification using 320-row area detector CT. Issue 1 (January 2019) - Takamura, Kazuhisa; Fujimoto, Shinichiro; Kawaguchi, Yuko; Kato, Etsuro; Aoshima, Chihiro; Hiki, Makoto; Kumamaru, Kanako K.; Daida, Hiroyuki
Abstract: Background: Although subtraction coronary computed tomography angiography (S-CCTA) has recently been developed to improve the diagnostic ability in patients with severe calcification, increase in radiation exposure remains a concern. The usefulness of S-CCTA using a low-radiation dose protocol was investigated. Methods: S-CCTA in 320-row area detector CT was performed on 84 consecutive patients with suspected obstructive coronary artery disease with Agatston score ≥100. Reconstruction and radiation dose were changed according to the slow filling time (SF) (137.5 ms < SF ≤ 262.5 ms. Half reconstruction without reduction of the current, 262.5 ms < SF ≤ 275 ms: automatic patient motion correction with 50% reduction, SF ≥ 275 ms: full reconstruction with 70% reduction) at a tube voltage of 100 kV. The percentage of patients with non-diagnostic stenosis of calcified coronary artery lesions was calculated in conventional (C-) CCTA, and S-CCTA was calculated based on 84 patients (446 segments) bases. In 27 patients (137 segments) examined by invasive coronary angiography (ICA), the diagnostic ability was investigated regarding the ICA findings as reference standard. Results: The percentage of non-diagnostic patients and segments on C-CCTA vs. S-CCTA was 40.5% vs. 9.5% and 16.4% vs. 2.9%, respectively. The Agatston score was 589.3 ± 655.3, and the total effective radiation dose (non-contrast scan and C-CCTA) was 2.7 ± 1.1 mSv. In the 27 patients, 137 segments area under the curve of S-CCTA (0.939, 95% CI: 0.895–0.983) for the ICA findings as reference standard was significantly higher than that of C-CCTA (0.785, 95% CI: 0.713–0.858) ( p  < 0.0001). Conclusion: The diagnostic ability of S-CCTA performed following the low-radiation dose protocol for patients with calcification was superior to that of C-CCTA alone.